HUBUNGAN SIKAP CARING PERAWAT DENGAN TINGKAT KEPUASAN PASIEN DI RUANG CENDANA II RSUD UNIT SWADANA PARE â KEDIRI TAHUN 2008 - Sukatmi, Sukatmi; Wati, Dwi Yohana (Akademi Keperawatan Pamenang, 2011)
The most important aspect of nursing care is the attitude and performance of nursing, but, in fact, by this time found some nurses not perform the caring aspect of nursing and they not perform nursing care as the patient need. The Â The purpose of this reseach is to know the relation of caring attitude of nurse with satisfaction of patient level at Cendana II room. Â Â Â Â In this reseach using cross sectional design with population is all patient at Cendana II room of RSUD Unit Swadana Pare â Kediri about 81 average responder each mounth, total of sampel is 67 responder by purposive sampling tehnique. The way of data collecting using kuesioner. Independent variable of caring attitude of nurse than dependen variable is patient satisfaction level.Â Â Â Â From result of Spearman Rho correlational test with SPSS get correlation result is 0,359 with sig (p) 0,003 with alfa 5% which show that 0,003 < 0,05 which show that H0 refused. So, there are relation between caring attitude of nurse with patient satisfaction level.Â Â Â Â With caring atitude of nurse more better in medical treatment, the patient will satisfied to the nurse service. From that data can conclusision that there is relation of caring attitude of nurse with patient satisfaction level. Hopely, nurse to more improve their caring in order the patient satisfied to treatment service.